ANALISIS CAMPUR KODE PADA MEDIA SOSIAL WHATSAPP (WA) - daka satia pinilih (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Language is a symbol of an arbitrary sound that is spoken with goals such as communication and opinion. Its role is very important, because by communicating humans can get information and knowledge. The researchers chose 10 students who mixed codes in giving private or group messages, which should either group messages or private message senders do not mix the code with local or foreign languages. Researchers aim to describe the code mix found on whatsapp social media which is currently a very popular communication tool. The research method used is descriptive qualitative. Research data taken were private and group messages on WA. From the results of the study note that the code mixing that occurs in the Whatsapp communication media in the form of phrases, words, and baster. The factors causing the occurrence of code mixing are due to the factors of the speaker's attitude and language that occurs.